Exendin‐4 shows no effects on the prostatic index in high‐fat‐diet‐fed rat with benign prostatic hyperplasia by improving insulin resistance. (10th March 2014) - Zheng, J.‐X.; Xiao, Y.‐C.; Hu, Y.‐R.; Hao, M.; Kuang, H.‐Y.
Summary Benign prostatic hyperplasia (BPH) is a prevalent disease globally, and accumulating evidence has indicated an association between BPH, insulin resistance (IR) and diabetes. Exendin‐4 is widely used in clinics, which could enhance the proliferation of pancreatic β cells. The ability of exendin‐4 to promote tumorigenesis has been of concern, and whether exendin‐4 would enhance the propagation of BPH is not fully understood. We aimed to determine whether glucagon‐like peptide‐1 receptors (GLP‐1Rs) were expressed in rat prostate and to determine the effect of exendin‐4 on prostate of BPH. Male Wistar rats were used and assigned to six groups: normal diet (ND), high‐fat diet (HFD), HFD + exendin‐4, HFD + BPH, HFD + BPH + exendin‐4 and HFD + BPH + rosiglitazone group. After castration, steroids were injected subcutaneously for 4 weeks to induce BPH. Rats were kept on high‐fat diet to induce IR. Treatment groups were treated with exendin‐4 and rosiglitazone. Prostatic index and HOMA‐IR index were used to evaluate the prostatic hyperplasia status and the degree of IR respectively. The expression of GLP‐1R was indicated not only by immunohistochemistry, but also by Western blot analysis. The expression of GLP‐1R was significantly higher, and HOMA‐IR index and body weight significantly decreased after administration of exendin‐4. However, no significant differences in the prostatic index were observed between exendin‐4 treatment groups and non‐exendin‐4 treatment groups. Prostatic index was not influenced by exendin‐4 maybe by improving IR and weight loss.